2016
DOI: 10.1074/jbc.m115.685040
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Phenylalanine in the Transmembrane Domain Enhances Heteromeric Interactions of Syndecans

Abstract: The transmembrane domain (TMD) of the syndecans, a family of transmembrane heparin sulfate proteoglycans, is involved in forming homo-and heterodimers and oligomers that transmit signaling events. Recently, we reported that the unique phenylalanine in TMD positively regulates intramolecular interactions of syndecan-2. Besides the unique phenylalanine, syndecan-2 contains a conserved phenylalanine (SDC2-Phe-169) that is present in all syndecan TMDs, but its function has not been determined. We therefore investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The presence of a unique phenylalanine residue Phe (167) has been shown to bestow to the SDC molecule increased ability to oligomerize and to regulate specific cell functions, including cell migration . In addition, the hetero‐oligomerization of SDC2 and SDC4 is heavily dependent on the conserved phenylalanine Phe (169), as the generated SDC2 (F169Y) mutant exhibits attenuation of downstream activities including cell migration and focal adhesion formation . This may be important in cancer cell behaviour, where formation of hetero‐dimers with SDC4 significantly affects SDC2‐mediated functions, as shown in migration and growth of colon cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a unique phenylalanine residue Phe (167) has been shown to bestow to the SDC molecule increased ability to oligomerize and to regulate specific cell functions, including cell migration . In addition, the hetero‐oligomerization of SDC2 and SDC4 is heavily dependent on the conserved phenylalanine Phe (169), as the generated SDC2 (F169Y) mutant exhibits attenuation of downstream activities including cell migration and focal adhesion formation . This may be important in cancer cell behaviour, where formation of hetero‐dimers with SDC4 significantly affects SDC2‐mediated functions, as shown in migration and growth of colon cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…1B). Backbone resonances including 15 N, 13 Ca, and 13 C' of residues from syndecan-2 excluding the artificial amino acids at the termini were fully assigned. Most Ha resonances were assigned based on a 3D-HBHACONH experiment.…”
Section: Secondary Structure Of Sdc2-tm In Dpc Micellesmentioning
confidence: 99%
“…5). The conserved residue F159 which was shown to be critical for dimerization [13] favored protein dimerization as its side chain could face to the same direction as the motif (Fig. 5).…”
Section: Structure Of Scn2-tm In Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed the potential of syndecan-2 and -4 to form hetero-oligomers, reducing each syndecan activity ( Choi et al, 2015 ). This hetero-oligomerization capacity may offer insight into an underlying modulating mechanism ( Kwon et al, 2015 ).…”
Section: The Transmembrane Domain-induced Oligomerization Properties mentioning
confidence: 99%